Destination Image as a Mediator between Digital Marketing, Leadership, Marketing Mix, and Tourist Satisfaction - Syafriani, Oza; Relifra, Relifra; Maulana, Fajar; Wahyuni, Cica; Zulbaidah, Zulbaidah (Amkop Management Accounting Review (AMAR), 2025)
This study investigates the role of destination image as a mediator in the relationships among digital marketing, leadership, the marketing mix, and tourist satisfaction. A total of 420 respondents participated in the survey, which was distributed both online and offline to tourists who visited various destinations in West Sumatra, Indonesia. The sampling technique employed was purposive sampling to ensure that respondents were relevant to the research context. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that digital marketing, leadership, and marketing mix exert significant positive effects on destination image. Furthermore, destination image significantly influences tourist satisfaction, confirming its pivotal role in shaping tourists’ overall experiences. Mediation analysis indicates that destination image partially mediates the relationships between digital marketing, leadership, marketing mix, and tourist satisfaction. Interestingly, the direct effect of leadership on tourist satisfaction was not statistically significant, suggesting that leadership influences satisfaction primarily through enhancing destination image. This study contributes to the tourism marketing literature by providing empirical evidence of the mediating role of destination image in the digital era. The results highlight the importance of integrated marketing strategies and leadership in strengthening destination image to enhance tourist satisfaction. Practical implications suggest that tourism stakeholders should optimize digital marketing tools, adopt effective leadership practices, and improve the marketing mix to build a strong destination image that fosters sustainable tourist satisfaction.